2005
DOI: 10.1017/s003118200500733x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing genetically diverse avian malarial infections using mixed-sequence analysis and TA-cloning

Abstract: Birds harbouring several malarial parasites are common in the wild, and resolving such multiple infections is important for our understanding of host-parasite relationships. We propose a simple and reasonably accurate method for detecting and resolving multiple infections, based on the analysis of parasite cytochrome b DNA sequences: genetically mixed infections are first identified by double nucleotide peaks on sequence electropherograms, and later retrieved by TA-cloning. We applied this method to wild birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 26 publications
(37 reference statements)
1
112
0
Order By: Relevance
“…Representatives of all lineages were also sequenced with the reverse primer. Multiple infections were resolved by examining if the most common lineage could be part of the multiple infection and from this comparison we subtracted the other sequence from the sites with double base calling (Pérez-Tris and Bensch 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Representatives of all lineages were also sequenced with the reverse primer. Multiple infections were resolved by examining if the most common lineage could be part of the multiple infection and from this comparison we subtracted the other sequence from the sites with double base calling (Pérez-Tris and Bensch 2005).…”
Section: Methodsmentioning
confidence: 99%
“…ospC and IGS alleles were named according to Bunikis et al (2004). Samples where sequences from any of the three loci had double peaks in the chromatogram at any nucleotide position were treated as multiple infections (Perez-Tris & Bensch, 2005) and excluded from further analyses. Mean genetic distance (P-distance) was calculated for the different loci using MEGA 4 (Tamura et al, 2007).…”
Section: Statistics and Genetic Analysismentioning
confidence: 99%
“…During the last ten years, the amplification of a specific part of the mitochondrial cytochrome b (cyt b) gene (Bensch et al 2000, Perkins and Schall 2002) has provided new opportunities in the studies of specificity, diversity, distribution, ecology and various aspects of phylogeny and evolution of avian haemosporidian parasites (Bensch et al 2000, Waldenström et al 2002, Beadell et al 2004, Fallon et al 2005. Recent papers have demonstrated that the diversity of cyt b lineages is much greater than that of the described morphospecies (Perkins and Schall 2002;Ricklefs and Fallon 2002;Waldenström et al 2002;Beadell et al 2004Beadell et al , 2006Bensch et al 2004;Pérez-Tris and Bensch 2005;Szymanski and Lovette 2005;Valkiūnas 2005). These studies suggest that many of the genetic lineages may represent distinct evolutionary entities .…”
Section: Introductionmentioning
confidence: 99%